The effect of olfactory and tactile cues on the evaluation of prescription-free pharmaceutical packaging: behavioural and psychophysiological modulations - Risso, Paola; Gallace, Alberto (European Journal of Applied Sciences, 2021)
Olfactory and tactile cues are considered two relevant aspects of product evaluation. The main aim of the study was to investigate the effects of these sensory modalities on the perception of four different over-the-counter prescription-free pharmaceutical products presented to participants in their packaging. We also aimed at comparing behavioural and physiological measures in assessing the participants’ reactions to the stimuli presented. In two experiments, we asked our participants to evaluate the products on a number of perceptual and semantic dimensions: reference market (male vs. female oriented), activation level (arousal), sensuality, pleasantness, and pharmaceutical/not pharmaceutical, using visual analogue scales (VAS). As a measure of physiological arousal, electrodermal activity was also measured. The results of our analysis showed significant modulatory effects of olfactory information over the participants’ behavioural responses. In particular, all the products were considered less reliable, less desirable, less sensual and less pleasant when presented together with the smell of truffle, as compared to conditions where they were combined with no scent or with the scent of strawberry. Intriguingly, the olfactory stimuli also affected the attribution of the reference market to the product. In particular, Durex Play Gel presented with truffle odour was evaluated by participants as more oriented to a feminine market, as compared to when presented with no odour or strawberry odour (the opposite effect was found with Antidry Calm). The experimental condition in which participant’s adopted a visual-tactile exploration of the prescription-free pharmaceutical products did not show significant effects. The analysis of the skin conductance responses showed different physiological patterns, compatible with certain perceived characteristics of the product presented (e.g., being more or less arousing).The latter results shows that physiological measures may not be always aligned with behavioural data.